State-Owned Banks, Stability, Privatization, and Growth : Practical Policy Decisions in a World Without Empirical Proof - Andrews, Michael (IMF Working Papers; Working Paper, 2005)
This paper provides an overview of the possible linkages between state-owned banks, privatization, and banking sector crises. Data on privatizations in over 65 countries is used together with data from the banking crisis literature to consider the relationship between state-owned banks and financial sector stability. The paper draws on the existing literature to provide guidance to policymakers regarding bank privatization.